A Facile Route for Synthesis of Structural Analogs for Latanoprost: An Anti-Glaucoma Agent - Harikrishna, M.; Rama Mohan, H.; Dubey, P.K.; Shankar, M.; V. Subbaraju, Gottumukkala (Asian Journal of Chemistry, 2011)
A facile synthetic approach has been developed for latanoprost analogs, (±) 13,14-dehydro latanoprost (2), (±) 16-nor-13,14-dehydro latanoprost (3) and (±) 16-homo-13,14-dehydro latanoprost (4) in five steps starting from key intermediate (5), through Wittig reaction and separation of diasteromers as the key steps.